Mothers' Experiences Interacting with Infants after Traumatic Childbirth. Issue 6 (November 2019) - Beck, Cheryl Tatano; Watson, Sue
Abstract: Purpose: The purpose of this study is to describe experiences of mothers interacting with their infants after traumatic childbirth. Study Design and Methods: A descriptive phenomenological method guided by Dahlberg, Dahlberg, and Nystrom's reflective lifeworld research was used. Women were recruited through Trauma and Birth Stress (TABS), a charitable trust in New Zealand, whose mission is to provide support for women who have experienced traumatic childbirth. Data were collected via an electronic survey. Women were asked to describe how their traumatic births affected their caring for and interactions with their infants and any other children they may have. Results: Eighteen women representing six countries across the globe participated. Four constituents of mothers' experiences interacting with their infants after traumatic births were identified: feelings of numbness and detachment, crying and anger, distressing cognitive changes, and limited outside social interactions. Clinical Implications: To help women struggling with the aftermath of their traumatic birth, nurses first need to identify them. Clinicians need to be attentive to symptoms such as a withdrawn, dazed look, and appearing distanced from their infants. Prior to hospital discharge after childbirth, women should be given opportunities to share their perceptions of their birth to determine if they view it as traumatic. Interventions should be started as soon as possible in this fragile mother–infant dyad to prevent long-term consequences. Abstract : During postpartum, prevalence of posttraumatic stress related to traumatic childbirth ranges from 4% in community samples to 18.5% in high-risk groups. Dr. Cheryl Beck, well known expert on childbirth trauma, and her colleague Sue Watson, present their study on mothers interacting with their babies after experiencing a traumatic childbirth. They offer suggestions for identifying traumatized new mothers in the inpatient setting and making referrals to mental health professionals.